If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x-5)=(4x-25)
We move all terms to the left:
(2x-5)-((4x-25))=0
We get rid of parentheses
2x-((4x-25))-5=0
We calculate terms in parentheses: -((4x-25)), so:We get rid of parentheses
(4x-25)
We get rid of parentheses
4x-25
Back to the equation:
-(4x-25)
2x-4x+25-5=0
We add all the numbers together, and all the variables
-2x+20=0
We move all terms containing x to the left, all other terms to the right
-2x=-20
x=-20/-2
x=+10
| 12.02=0.6h | | -7v-4v=-11 | | 2x^2+8x=72 | | y/5+16=34 | | -6x=-8-2x | | d/19+6=7 | | x+40°=180° | | 4x+12-3x=38 | | 3a-16=32 | | 16=-2+3b | | x2-5/2=15 | | x+68+2x-68=180 | | 2=x/3+6 | | ÷3(10+2x)=4 | | 2x+21=31 | | x+68=2x-68=180 | | 249=0.04x+9 | | (10+2x)÷3=4 | | x+3+6=16 | | 3x^2-16=180 | | 5x+3(2x-3)=9x-5+2x | | 4x-7-2x=5 | | x+2x+4x=7x= | | x-22=2x-60 | | x3+3x2-5x-15=0 | | 11x-48=7x | | 3x-42=5x-100 | | x+2x+4x=7x=14 | | 9(w-9)-2=-7+7(w-8 | | 9x+8-12=3x+2 | | 5x-79+4x-92=180 | | 8x-6=5x+128x−6=5x+12 |